Assessment of the operational impact of the Barbados VAT between 1997 and 2001 - Alleyne, Philmore (2003)
Examines and analyzes the operational impact of the Value Added Tax (VAT) in Barbados for the period 1997-2001. Reveals that the introduction of VAT in Barbados has proven to be a successful system of tax collection. Notes that it has achieved its goals of broadening the tax base and increasing tax revenue.